2009
DOI: 10.1021/es8036725
|View full text |Cite
|
Sign up to set email alerts
|

Mass Flows of X-ray Contrast Media and Cytostatics in Hospital Wastewater

Abstract: Little is known about the significance of hospitals as point sources for emission of organic micropollutants into the aquatic environment. A mass flow analysis of pharmaceuticals and diagnostics used in hospitals was performed on the site of a representative Swiss cantonal hospital. Specifically, we analyzed the consumption of iodinated X-ray contrast media (ICM) and cytostatics in their corresponding medical applications of radiology and oncology, respectively, and their discharge into hospital wastewater and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(89 citation statements)
references
References 31 publications
1
87
0
Order By: Relevance
“…The total delivered amount of anticancer agents as pollutants comes from hospital sewage and municipal wastewater due to improper disposal by the patients [6]. A Swiss study using a mass flow analysis of cytostatic compounds demonstrated that only 1.1-3.7% of the excreted amount of these compounds was found in the hospital effluent [7]. This result is consistent with the input pathways for anticancer drugs in the aquatic as shown in table 1 [8].…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…The total delivered amount of anticancer agents as pollutants comes from hospital sewage and municipal wastewater due to improper disposal by the patients [6]. A Swiss study using a mass flow analysis of cytostatic compounds demonstrated that only 1.1-3.7% of the excreted amount of these compounds was found in the hospital effluent [7]. This result is consistent with the input pathways for anticancer drugs in the aquatic as shown in table 1 [8].…”
Section: Introductionsupporting
confidence: 72%
“…However, the mechanism of action is not fully elucidated. Temozolomide is a prodrug of monomethyl triazeno imidazole carboxamide, which can readily methylate N 7 or O 6 positions of guanine residues and lead to tumor cell apoptosis [34]. Carmustine, lomustine, and temozolomide are hydrophobic and able to cross the blood brain barrier.…”
Section: Nonclassical Alkylating Agents (Platinum Compounds): Cisplatmentioning
confidence: 99%
“…Nevertheless, concentrations of one order of magnitude higher were reported in effluents from a hospital in Switzerland (Weissbrodt et al, 2009). …”
Section: Occurrence Of Pharmaceuticals In Hospital Effluentsmentioning
confidence: 99%
“…These changes will have impact on pharmaceuticals detected in hospital effluents, since they are closely related with the substances that are being administered in a certain hospital as well as their quantities. Several authors have shown the presence of pharmaceuticals in hospital wastewaters (Gómez et al, 2006;Lin and Tsai, 2009;Sim et al, 2011;Verlicchi et al, 2012a;Weissbrodt et al, 2009). Furthermore, hospital effluents also play an important role in the introduction of pathogens into public wastewaters, especially concerning multi-resistant bacteria, contributing to the spread of antibiotic resistance into the environment (Kümmerer, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Hospitals as potential 'hotspots' for the discharge of certain pharmaceuticals are included in households, since they usually discharge into the same sewer system and are thus treated together. Although the consumption of pharmaceuticals in hospitals is elevated, their excretion may also occur in households (Weissbrodt et al, 2009). Some recalcitrant indicator substances (e.g.…”
Section: Requirements For Indicator Substancesmentioning
confidence: 99%